Humanistic Principal Leadership in Inclusive Early Childhood Education: A Qualitative Exploration - Maulana, Selamat; Aslamiah, Aslamiah; Noorhapizah, Noorhapizah; Novitawati, Novitawati; Nisa, Uswatun; Thai, Aom (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Humanistic principal leadership is essential for fostering inclusive Early Childhood Education (ECE), yet remains underexplored in Indonesia’s inclusive schools. This study examined how principals practice humanistic leadership in two inclusive kindergartens in Banjarmasin, South Kalimantan, to support diverse learning environments. Using a descriptive qualitative design, data were gathered through observation, in-depth interviews with two principals, eight teachers, four parents, and document analysis at Pelita Hati and Bina Sejahtera Kindergartens. Thematic analysis followed Miles and Huberman’s framework. Results show humanistic leadership is reflected in embracing diversity, building supportive environments, and facilitating collaboration. Principals lead through participatory decision-making, empathy, care, and promoting each child’s potential, shaping an inclusive, humanistic school culture. The study offers insights into how humanistic leadership operates in inclusive ECE, providing a practical reference for principals and policymakers to strengthen inclusive, child-centered education.